Vertical analysis of patients with late lower arch crowding - Sami K Al-Joubori; Ali M Al-Attar; Mustafa M Al-Khatieeb (College of Dentistry/ University of Baghdad, 2014)
Background: Because of many factors play a role in the developing of late lower arch crowding, therefore the objective of the current study is to do vertical analysis for subjects with late lower dental arch crowding. The conducted study is the first attempt to do vertical analysis for Iraqi subjects with late lower arch crowding to see if there is a vertical discrepancy in such patients. Subjects and methods: Eighty subjects were selected according to certain inclusion criteria from patients attending the Orthodontic Department in the College of Dentistry, Baghdad University, patients ranged between 18-25 years old. The 80 patients were divided into two groups (crowding and normal), 40 patients each (20 males and 20 females). A study cast of lower dental arch was obtained, and then Nance's space analysis made for each cast, Cephalometric radiographs were also taken for each patient involved in the current study and digitization was done to calculate nine vertical linear and twelve angular measurements. Results: Most of linear measurements showed higher mean values in crowding than normal subjects except S-Go, Ar-Go, and PFH/AFH, also subjects with crowding had significantly higher (P